INFLUENCE OF ETHICS, TAX SANCTIONS, TAX SYSTEM MODERNIZATION AND TRANSPARENCY ON TAX COMPLIANCE (Case Study of Individual Employee Taxpayers in Subang Regency) - Lina Putri Selina (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study aims to determine the effect of ethics, tax sanctions, system modernization, and tax transparency on tax compliance. This research was conducted on individual employee taxpayers in Subang district. The population in this study were 100 individual taxpayer employees in Subang district. The data used in this study is primary data obtained by distributing online questionnaires via google form. The data analysis technique used is descriptive analysis method, data quality test, classical assumption test and hypothesis testing. The results of this study indicate that Ethics does not have a negative effect on Tax Compliance, Tax Sanctions do not have a positive effect on Tax Compliance, System Modernization and Tax Transparency have a positive effect on Tax Compliance.